The corporate blog as an emerging genre of computer-mediated communication : features, constraints, discourse situation - Puschmann ,Corneliuseauthor (Universitèatsverlag Gèottingen, 2010)
Digital technology is increasingly impacting how we keep informed, how we communicate professionally and privately, and how we initiate and maintain relationships with others. The function and meaning of new forms of computer-mediated communication (CMC) is not always clear to users on the onset and must be negotiated by communities, institutions and individuals alike. Are chatrooms and virtual environments suitable for business communication? Is email increasingly a channel for work-related, formal communication and thus ""for old people"", as especially young Internet users flock to Social Networking Sites (SNSs)? Cornelius Puschmann examines the linguistic and rhetorical properties of the weblog, another relatively young genre of CMC, to determine its function in private and professional (business) communication. He approaches the question of what functions blogs realize for authors and readers and argues that corporate blogs, which, like blogs by private individuals, are a highly diverse in terms of their form, function and intended audience, essentially mimic key characteristics of private blogs in order to appear open, non-persuasive and personal, all essential qualities for companies that wish to make a positive impression on their constituents.BR‰